ANALYSIS OF REPRODUCTIVITY OF MADRASIN CATTLE BEFORE AND AFTER FOOT AND MOUTH DISEASE ON GILI IYANG ISLAND, SUMENEP, MADURA - Zulfah; Sabdoningrum, Emy Koestanti; Hidanah, Sri; Lokapirnasari, Widya Paramita; Mufasirin; Yudanianyi, Ira Sari (Jurnal Biosains Pascasarjana, 2025)
This research aims to analyze reproductivity (S/C and Pregnancy) and supply and demand for Madrasin cattle before and after FMD disease on Gili Iyang Island, Sumenep, Madura. This research used data from 450 madrasin cattle on Gili Iyang Island, Sumenep. The research was carried out by comparing data obtained before the FMD outbreak in January 2022 – May 2022 and after the FMD outbreak in June 2022 – November 2022. The results of the research showed that the reproductivity of Madrasin cattle before and after the FMD disease on Gili Iyang Island, Sumenep, Madura in S/C increased, while during pregnancy there is a decrease. The supply and demand for the Madrasin cattle business before and after the FMD on Gili Iyang Island, Sumenep, Madura, decreased.